Introductory econometrics : A modern approach / Jeffrey M. Wooldridge - Wooldridge, Jeffrey M., 1960-
Wooldridge uses a systematic approach motivated by the major problems facing applied researchers. This text provides important understanding for empirical work in many social sciences, as well as for carrying out research projects.